2015
DOI: 10.3945/ajcn.115.108159
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of soluble fiber and risk of islet autoimmunity by 5 y of age: results from the TEDDY study

Abstract: Background: Deficient soluble fiber intake has been suggested to dysregulate the immune response either directly or through alterations of the microbial composition in the gut. Objective: We hypothesized that a high intake of dietary soluble fiber in early childhood decreases the risk of type 1 diabetes (T1D)-associated islet autoimmunity. Design: We analyzed 17,620 food records collected between age 9 and 48 mo from 3358 children from the United States and Germany prospectively followed in the TEDDY (The Envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…Soluble dietary fiber intake during infancy and childhood was not associated with the risk of islet autoimmunity in the German and US children from the TEDDY study .…”
Section: Fetal Exposuresmentioning
confidence: 85%
See 1 more Smart Citation
“…Soluble dietary fiber intake during infancy and childhood was not associated with the risk of islet autoimmunity in the German and US children from the TEDDY study .…”
Section: Fetal Exposuresmentioning
confidence: 85%
“…Several types of dietary exposures at different stages of life may be connected to the development of preclinical and clinical type 1 diabetes (Table , Refs. ). Already, maternal diet during pregnancy may affect the development of this disease .…”
Section: Suspected Risk and Protective Factors Of Pre‐ Or Clinical Tymentioning
confidence: 97%
“…To our knowledge, no previous studies exist on the association between oat intake and the risk of IA or T1D. Two previous prospective studies found no association between children's total 22 and soluble 21 dietary fiber intake and IA. Differences in the results compared with this study may be explained by different outcome variables, food varied from 75.4% at 6 months to 92.6% at 1 year for oats; 52.7% at 6 months to 75.3% at 6 years for rice; 56.2% at 6 months to 98.9% at 6 years for wheat; 33.8% at 6 months to 92.1% at 6 years for rye; and 31.8% at 6 months to 60.1% at 1 year for barley.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…Exposure to probiotics in early infancy was found to decrease the risk of IA in the highest risk children [9], while use of hydrolyzed infant formula increased the risk of IA [13]. Intake of soluble fiber is not associated with IA [16]. We have reported differences in supplement use, diet, and feeding patterns by country, sociodemographic status, and diabetes status of the parents [6871].…”
Section: Results In Major Study Areasmentioning
confidence: 99%
“…TEDDY aims to identify environmental factors that trigger or protect against the development of IA and T1D. The uniquely intensive follow-up of TEDDY children has already evaluated a number of environmental triggers [8•, 9-16], gene variants [1721], and gene-environment interactions involved in the appearance of islet autoantibodies [22•, 23, 24•] preceding T1D. Models emerging from current data suggest that either a variety of exposures act on a similar pathway or that there are multiple pathways leading to the destruction of beta-cells.…”
Section: Introductionmentioning
confidence: 99%